2013
DOI: 10.1002/mrd.22174
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization of the actin regulatory protein palladin in sertoli cells

Abstract: In the testis, F-actin structures are involved in spermatid nuclear remodeling and cytoplasm reduction, maintenance of the blood-testis barrier, support of the spermatogonial stem cell niche, and release of spermatids into the tubular lumen. To gain a better understanding of actin regulation in Sertoli-germ cell interactions, we investigated the expression of the Palladin (Palld) gene, which encodes a widely expressed phosphoprotein that localizes to actin-rich cytoplasmic structures, including focal adhesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 41 publications
1
19
1
Order By: Relevance
“…We previously showed that PALLD relocates from the cytoplasm to nuclei of Sertoli cells as they undergo terminal differentiation (Niedenberger et al 2013). This predominant nuclear localization was also indicated in a report published at the same time (see Fig.…”
Section: Introductionmentioning
confidence: 49%
See 4 more Smart Citations
“…We previously showed that PALLD relocates from the cytoplasm to nuclei of Sertoli cells as they undergo terminal differentiation (Niedenberger et al 2013). This predominant nuclear localization was also indicated in a report published at the same time (see Fig.…”
Section: Introductionmentioning
confidence: 49%
“…1B, Supplementary Figure S2A, see section on supplementary data given at the end of this article), but was mostly nuclear in Sertoli cells isolated from 18 dpp mice (Fig. 1C, Supplementary Figure S2B), as was seen in vivo (Niedenberger et al 2013). It was previously shown that Sertoli cell morphology and cytoskeletal organization were modified in vitro by the addition of serum to culture media (Hutson et al 1980).…”
Section: Palld Localization Is Dynamic In Primary Sertoli Cellsmentioning
confidence: 87%
See 3 more Smart Citations